Penanda Jamak (Perbandingan Antara Bahasa Arab Dan Bahasa Indonesia) - Arif Humaini (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2017)
Indonesian and Arabic language are different languages ​​, both these languages ​​each have different systems at the level of phonemes, morphemes, phrases, clauses, and sentences. The Arabic language included in flection language, while Indonesian language is not. Flection language is defined as the process or result of adding affixes to the base or root word for limiting its grammatical meaning. Therefore, the presence of the marker in Arabic was deemed paramount, while Indonesian concerned with word order. A marker is a tool that serves as affixes to express grammatical feature or function words. Matching the appropriate marker in Arabic is called al - 'alamat. There are many kinds of markers in Arabic, as there is a gender marker (mu'annats and mudzakkar), mufrod markers, plural markers, and so on. In this paper, we only specialize in the plural marker. Plural marker in Indonesian mostly expressed in the form of reduplication consisting of nouns, verbs, and adjectives. Also with the use of the word number by using ‘penyukat’ which can indicate the plural of a word. In the Arabic language, the process of forming the plural marker is characterized by three things: (1) replace the letters or ‘harakat’, (2) eliminate one of the letters, and (3) providing additional or affixes, in front of , in the middle, or at the end of the word.